A55 GIS based Walkability Index for Urban Contexts. Application to Luxembourg. Issue 2 (June 2015) - Klein, Olivier; Gutiérrez, Guillermo; Escobar, Francisco
Abstract: Background: For a few years, walkability has been identified as an important component of efficient, accessible and healthy neighbourhoods. Furthermore, many policy interventions promote participation in physical activity particularly through active mobility. Numerous studies demonstrate the impact of neighbourhood environments on the practice of walking. The aim of this study is to assess the neighbourhoods' walkability of an elderly cohort in Luxembourg. In the framework of a research project about healthy ageing (CURHA project), we propose a new and objective measure of walkability based on a GIS approach at micro level. Methods: Three main steps are required to compute the proposed index. (1) Delimitation of the potential walking areas. A pedestrian network has been built on the whole Grand-Duchy of Luxembourg. Starting from a Digital Elevation Model, this network integrates topography. Such addition allows to modulate the theoretical speed of the pedestrians according to the slope and delimitate more precisely the potential walking areas based on a fixed access time (15 min from home). (2) Computation of walkability attributes. Within these delimited areas, several attributes of the final indicator can be computed: connectivity, population density, land use mix, proximity and diversity of amenities, and greenness measured by a vegetation index. (3) Construction of the synthetic indicator. A synthetic indicator combining all these attributes is then produced. It takes the form of a standardized ranking indicator from 0 to 100, qualifying the potential of walkability of given addresses (home). Results: The walkability index was firstly calculated, at an individual level, for residential addresses of 500 participants of the CURHA survey in Luxembourg. Secondly, this index has been extended on the whole country of Luxembourg. This second case let us consider possible transnational comparisons to other countries or metropolitan areas, depending on the availability of the data. From a thematic point of view, significant contrasts can be identified mainly in the suburban areas. The degree of urbanity – presence and density of amenities – and the topography – reducing the accessible areas – can partly explain these differences. Conclusions: The walkability index methodology provided in this study contributes to enhance and complement the subject matter. It provides a reliable objective notion about the nature of the built environment features significantly associated to healthy ageing. However, these findings require further validation. A survey on 500 residents is currently underway in order to confront objective measures of walkability with respondents' practices, perceptions and attitudes.